Combining task‐related activation and connectivity analysis of fMRI data reveals complex modulation of brain networks. Issue 11 (7th August 2017) - Gerchen, Martin Fungisai; Kirsch, Peter
Abstract: Task‐related effects in functional magnetic resonance imaging (fMRI) data are usually analyzed with local activation approaches or integrative connectivity approaches, for example, by psychophysiological interaction (PPI) analysis. While both approaches are often applied to the same data set, a systematic combination of the results with a whole‐brain (WB) perspective is rarely conducted and the relationship between task‐dependent activation and connectivity effects is relatively unexplored. Here, we combined brain activation and graph theoretical analysis of WB‐PPI results in an exemplary episodic memory data set of N = 136 healthy human participants and found regions with congruent as well as incongruent activation and connectivity changes between task and control conditions. A comparison with large‐scale resting state networks showed that in congruent as well as incongruent regions task‐positively modulated connections were mainly between‐network connections, especially with the default mode network, while task‐negatively modulated connections were mainly found within resting state networks. Over all regions, the strength of absolute activation effects was associated with the tendency to exhibit task‐positive connectivity changes, mainly driven by a strong relationship in negatively activated regions. These results demonstrate that task demands lead to a complex modulation of brain networks and provide evidence that task‐evoked activation and connectivity effects reflect separable and complementary information on the macroscale brain level assessed by fMRI. Hum Brain Mapp 38:5726–5739, 2017 . ©2017 Wiley Periodicals, Inc.